Effect of starting stance on sprint time in NAIA volleyball players - Johnson, T.; Brown, L. E.; Coburn, J. W.; Judelson, D. A.; Khamoui, A. V.; Uribe, B. P.; Tran, T. (The Journal of Strength and Conditioning Research, 2010)
Foot position (i.e. starting stance) likely plays an important role in influencing short-distance sprint speed, and therefore, the ability to reach a ball. The purpose of this study was to evaluate four different starting stances on sprint speed. Twenty-six NAIA collegiate volleyball players, (age men 20.85 +/- 2.79 yrs, women 19.31 +/- 1.25 yrs, height men 191.28 +/- 8.51cm, women 179.16 +/- 7.73cm, mass men 83.52 +/- 11.77kg, women 69.43 +/- 9.74kg) volunteered to participate in one testing session. Each subject warmed up with a 3-lap jog around the volleyball court. Following warm-up, subjects performed twelve 15ft sprints, completing three trials each of four starting stances (parallel [P], false-step [FS], staggered [S], and staggered false-step [SFS]). Investigators randomized stance order. A 2 x 4 (sex x condition) mixedfactor repeated measures ANOVA revealed there was no significant interaction of sex and condition; however, there were main effects for sex and condition. The main effect for sex demonstrated that males were faster than females. Players ran significantly slower using the P stance (1.25 +/- 0.09 s) than any other starting stance (SFS = 1.14 +/- 0.06 s, S = 1.16 +/- 0.07 s, FS = 1.18 +/- 0.10 s). The SFS stance produced faster speeds than the FS stance. This study indicates that starting with a staggered stance (whether employing a false step or not) produces the greatest sprinting velocity over the initial 15ft. Although taking a false-step seems counterproductive, the resultant stretch-shortening cycle likely increases force production of the push off phase and therefore, sprint speed. The S stance might produce greater speeds by reducing movement time in response to a stimulus. Volleyball players might increase their sprint speed by utilizing either a staggered false-step or a staggered stance prior to accelerating.